STRATEGI PENGEMBANGAN PENYULUHAN PERTANIAN DI KABUPATEN SEMARANG JAWA TENGAH The Development Strategy Of Agricultural Extension In The District Of Semarang Central Java - Sasongko, Bayu; Satmoko, riroso; Mukson, Mukson (Jurnal Pengembangan Penyuluhan Pertanian, 2018)
This study was aimed to analyze the implementation of agricultural extension in Semarang Regency, analyze the strengths, weaknesses, opportunities and threats of agricultural extension activities in Semarang Regency, also analyze the position and determine the strategy to be implemented in developing agricultural extension in Semarang Regency. The research used a survey method and located in Semarang Regency, Central Java. This research was conducted in November 2016 to May 2017 using 99 Respondents and 6 people as a key person respondents. Factors affected the development of agricultural extension in Semarang Regency consists of five strengths factors, five weakness factors, five opportunities factors, and five threats factors. Alternative strategies were develop using SWOT analysis and prioritization strategy was determined using AHP (Analytical Hierarchy Process) with expert choice version 11 program. The result showed that the development strategy of agricultural extension in Semarang Regency using S-O strategy along with priority strategy, namely (1) a proposal to the government for enacted regulations that have a positive impact on farmers with 0,299 in value, in the form of government regulations to give agriculture product price assurance, (2) Optimizing the performance of extension workers to conduct a training to the farmers by approaching farmer groups with 0,245 in value, could be conducted by technical inventiveness extension in district level, visitation and supervision, farmer discussion in district level, and farmers field day, (3) Utilizing the community positive perception to optimize the performance of agricultural extension with 0,156 in value, through the certification of agricultural extension as a formal recognition to competent counselor in their duties, (4) Conduct a training and extension activities to improve farmers skills and knowledge with 0,150 in value, through training and visitation approach, (5) Utilizing technology innovations development to optimize the role and function of the extension services in each region with 0,150 in value by means ofagricultural technology dissemination produced by the Research and Development of the Ministry of Agriculture.Keywords: Strategy, Counseling, Strength, Weakness, Opportunities, Threats